Role of platelet TLR4 expression in pathogensis of septic thrombocytopenia - Wang, Yong-qiang (Second Affiliated Hospital of Zhejiang University School of Medicine, 2011)
BACKGROUND: Infection-induced thrombocytopenia (TCP) is an independent risk factor for death of patients with sepsis, but its mechanism is unknown. This study aimed to explore the underlying mechanism of TCP based on the relationship between TLR4 expression and platelet activation in septic patients. METHODS: A total of 64 patients with sepsis were prospectively studied. Platelet count (PC), mean platelet volume (MPV), platelet distribution width (PDW), platelet TLR4 expression, platelet PAC-1 expression, sCD40L and TNF-α concentrations were compared between the healthy control group (15 volunteers) and sepsis group (64 patients) at admission and on the 3, 5, and 9 days after admission. The changes of MPV and PDW in the TCP and non-TCP subgroups of sepsis before and after treatment were recorded. Prognostic index was analyzed. RESULTS: PC was lower in the sepsis group (P=0.006), and MPV and PDW were higher in the sepsis group than those in the healthy control group (P=0.046, P=0.001). Platelet TLR4 and PAC-1 expressions, and sCD40L and TNF-α levels increased more significantly in the sepsis group (P<0.001). PAC-1 expression and TNF-α level were higher in the TCP group than in the non-TCP group before and after treatment (P=0.023, P=0.011). sCD40L concentration and platelet TLR4 expression were significantly higher in the treated TCP group than in the non-TCP group (P=0.047, P=0.001). Compared to the non-TCP group, the rate of bleeding was higher (P=0.024) and the length of ICU stay was longer (P=0.013). The APACHE II score and the 28-day mortality were higher in the TCP group (P<0.01, P=0.048). CONCLUSIONS: The elevation of platelet TLR4 expression in sepsis along with platelet activation is closely related to the incidence of thrombocytopenia. The occurrence of TCP is a sign of poor prognosis in sepsis patients.